The Effectiveness of Using a Digital Learning System (DLS) Through a Talking Stick Type Cooperative Learning Model in Social Studies Subjects for Class V Elementary School - Nanda, Ficha Aulia; Sitompul, Hamela Sari (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Following a breakthrough in the development of learning technology, the Digital Learning System (DLS) is a breakthrough in developing learning technology where students can take advantage of technology in the form of software or hardware, online or offline, that is packaged attractively and interactively. This study aimed to determine the effectiveness of using DLS through the Talking Stick in terms of learning motivation and student learning outcomes. This research is descriptive analysis research with a quantitative approach; namely, the data obtained is quantitative data that will be analyzed descriptively. The sample used in this study is fifth-grade elementary school students, as many as 14 students in social studies subjects. The research was conducted at SD Negeri 124405 Pematang Siantar. The results showed that 78.58% of students already had learning motivation, and 85.71% of student learning outcomes passed the KKM. Based on these data, using the Digital Learning System Cooperative learning model Talking Stick has been said to be effective in motivation and student learning outcomes in class V SD Negeri 124405 Pematang Siantar.